2015
DOI: 10.1016/j.ecoenv.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of cytotoxicity endpoints and test microalgal species to disclose the toxic effect of common aquatic pollutants

Abstract: Pulse discharges of chemicals to aquatic environments may lead to high concentrations of them in surface waters for short periods of time, but enough to induce toxic effects on aquatic organisms; however, no many methods allow an early warning of toxicity of these agents. Acute effects of one representative chemical from each of three of the main groups of aquatic pollutants (pesticides, metals and pharmaceuticals) are studied on two green microalgal species (Chlamydomonas moewusii and Chlorella vulgaris). Flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…These results could potentially be explained by growth data at 24 h, since a reduction about 50% of the growth was observed in the cultures exposed to atrazine with respect to control cultures. Our results confirm previous findings regarding a decline in esterase activity in Chlamydomonas cells exposed to different herbicides (Jamers and De Coen, 2010;Nestler et al, 2012;Prado et al, 2009a) and other aquatic pollutants (Prado et al, 2015). Obtained results could indicate that the mechanism of action of atrazine generates oxidative stress that causes redox misbalances and alterations in protein synthesis and, therefore, a general decrease in cellular activity.…”
Section: Cellular Metabolic Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…These results could potentially be explained by growth data at 24 h, since a reduction about 50% of the growth was observed in the cultures exposed to atrazine with respect to control cultures. Our results confirm previous findings regarding a decline in esterase activity in Chlamydomonas cells exposed to different herbicides (Jamers and De Coen, 2010;Nestler et al, 2012;Prado et al, 2009a) and other aquatic pollutants (Prado et al, 2015). Obtained results could indicate that the mechanism of action of atrazine generates oxidative stress that causes redox misbalances and alterations in protein synthesis and, therefore, a general decrease in cellular activity.…”
Section: Cellular Metabolic Activitysupporting
confidence: 93%
“…These results together viability data indicate that the induced damage in the plasma membrane begins with changes in the permeability properties (depolarization) before the disruption of the membrane integrity (Prado et al, 2012b(Prado et al, , 2015. Previous studies in different microorganisms have also reported this change in the permeability of the cytoplasmic membrane (Bouix and Ghorbal, 2015;Lloyd et al, 2004;Wickens et al, 2000).…”
Section: Cytoplasmic and Mitochondrial Membrane Potentialssupporting
confidence: 68%
“…Microalgae have been frequently used in ecotoxicological screening of contaminated water, and also as test microorganisms for in vitro toxicity bioassays due to their characteristics and position in the aquatic food web. Previous studies about the toxic effects of different pollutants on microalgal physiology ( Esperanza et al, 2015a;Prado et al, 2015;Prado et al, 2012;Rioboo et al, 2009 ;Cid et al, 1996) demonstrate that flow cytometric analyses can be an alternative to standard algal population-based endpoints, since it allows a rapid, quantitative and simultaneous measurement of multiple responses to toxic stress in individual algal cells near in vivo conditions. Furthermore, the marine microalgal species used in the present work, Tetraselmis suecica, has been previously used to study the toxic effect of different antibiotics showing a high sensitivity ( Seoane et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This realization has resulted in a shift from (chemical-based) contaminant monitoring towards reliance on (effect-based) ecotoxicity testing using biological assays (Lam and Gray, 2003). Among the intracellular toxicity alterations that can be induced by chemicals, reactive oxygen species (ROS) production and DNA damage are currently the best accepted paradigms to assess and compare the toxicity of different environmental contaminants, since recent evidence has shown that many types of chemicals exhibit oxidative and/or genotoxic potential on living organisms such as unicellular algae (Cirulis et al, 2013, Hess, 2000Prado et al, 2009Prado et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, considerable research efforts have been directed towards incorporating a suite of more specific molecular, biochemical and physiological endpoints which can provide early warning signals for possible hazardous effects induced by chemical exposure in unicellular algae. In this regard, previous studies have reported the implementation of flow cytometry (FCM) in toxicity bioassays with microalgae as an alternative to traditional techniques, assessing the biological effects of several environmental pollutants (Adler et al, 2007, Franklin et al, 2004, Franqueira et al, 2000, Hankamer et al, 2014, Jamers and De Coen, 2010Prado et al, 2009Prado et al, , 2012aPrado et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%